A3.34 The global microrna profile of skin in systemic sclerosis. (31st January 2014) - Salazar, G A; Assassi, S; Wu, M; Hagan, J; Mayes, M D
Abstract : Background: The underlying pathogenesis of systemic sclerosis (SSc) remains poorly understood contributing to limited efficacy of therapeutic options. MicroRNAs (miRNAs) are small non-coding RNAs that play an important role in post-transcriptional gene regulation. 1, 2 Two families of dysregulated miRNAs, miR-21 and miR-29, have been implicated in the pathogenesis of fibrotic diseases and replicated in SSc. 3–6, 7, 9 These studies focused on a miRNA of interest and global skin miRNA profiling in SSc has not been reported. Recent advances in quantitative polymerase chain reaction (qPCR) allow simultaneous measurement of hundreds of miRNAs. The objective of this study was to use this technology to identify the unbiased, global miRNA profiling of SSc skin and evaluate their potential role in its pathogenesis. Methods: We investigated the miRNA profile in SSc skin compared to unaffected controls using multiplex qPCR platform. We obtained forearm skin samples (3 mm punch biopsy) from 10 patients with early SSc (< 5 yrs, on no immunosuppression) and 10 age-, gender- and ethnicity matched controls. Total RNA was isolated using Qiagen miRNAeasy mini kit and examined by Exiqon LNA-enhanced (locked nucleic acid) miRNA qPCR. Levels of 752 miRNAs were determined. Unsupervised hierarchical clustering analysis was performed. Patient and control sample miRNA levels were compared and differences with a p<0.01, false discovery rate (FDR) <10% and fold change >2 were considered statistically significant. Results: The unsupervised hierarchical clustering analysis showed that the miRNA skin profile almost perfectly separated SSc patients and controls. Only one patient clustered along with controls (Figure 1 ). Comparison of patient to control samples revealed 26 miRNAs that were differentially expressed. Eighteen of these (69%) were part of the largest known human miRNA cluster (miR-379/miR-656) located on chromosome 14q32.3. 10 Three miRNAs were encoded in a cluster on chromosome X (Xq26.3). We confirmed the previously reported up-regulation of miR21-5p in SSc. 7, 9 Conclusions: To our knowledge, this is the first global, unbiased examination of miRNAs in SSc skin. The miRNA profile almost perfectly separated SSc patients and controls. We observed 26 dysregulated miRNAs, most of them coming from two clusters, one of them located in chromosome X. This finding might have important biological implications considering the female predilection of SSc. Dysregulation of these miRNA clusters have not been reported in SSc and other autoimmune diseases. The results of our study link miRNA to the pathogenesis of SSc and could have important ramifications for future drug and biomarker development. References: van RE. The art of microRNA research. Circ Res 2011;108(2):219-234. Chuang JC, Jones PA. Epigenetics and microRNAs. Pediatr Res 2007;61(5 Pt 2):24R-29R. Vettori S, Gay S, Distler O. Role of MicroRNAs in Fibrosis. Open Rheumatol J 2012;6:130-139. Pandit KV, Milosevic J, Kaminski N. MicroRNAs in idiopathic pulmonary fibrosis. Transl Res 2011;157(4):191-199. Jiang X, Tsitsiou E, Herrick SE, Lindsay MA. MicroRNAs and the regulation of fibrosis. FEBS J 2010;277(9):2015-2021. Chau BN, Brenner DA. What goes up must come down: the emerging role of microRNA in fibrosis. Hepatology 2011;53(1):4-6. Zhu H, Li Y, Qu S et al. MicroRNA expression abnormalities in limited cutaneous scleroderma and diffuse cutaneous scleroderma. J Clin Immunol 2012;32(3):514-522. Maurer B, Stanczyk J, Jungel A et al. MicroRNA-29, a key regulator of collagen expression in systemic sclerosis. Arthritis Rheum 2010;62(6):1733-1743. Zhu H, Luo H, Li Y et al. MicroRNA-21 in Scleroderma Fibrosis and its Function in TGF-beta- Regulated Fibrosis-Related Genes Expression. J Clin Immunol 2013;33(6):1100-1109. Laddha SV, Nayak S, Paul D et al. Genome-wide analysis reveals downregulation of miR-379/miR-656 cluster in human cancers. Biol Direct 2013;8:10. Zhang L, Volinia S, Bonome T et al. Genomic and epigenetic alterations deregulate microRNA expression in human epithelial ovarian cancer. Proc Natl Acad Sci U S A 2008;105(19):7004-7009. Haller F, von HA, Zhang JD et al. Localization- and mutation-dependent microRNA (miRNA) expression signatures in gastrointestinal stromal tumours (GISTs), with a cluster of co-expressed miRNAs located at 14q32.31. J Pathol 2010;220(1):71-86. Luk JM, Burchard J, Zhang C et al. DLK1-DIO3 genomic imprinted microRNA cluster at 14q32.2 defines a stemlike subtype of hepatocellular carcinoma associated with poor survival. J Biol Chem 2011;286(35):30706-30713.